PENGEMBANGAN KARAKTER KEPEMIMPINAN DI PENDIDIKAN DASAR MELALUI PERAN ORGANISASI SISWA: INTEGRASI NILAI-NILAI KEMUHAMMADIYAHAN - Umami, Izza; Malik Fajar, Dien Nurmarina (Jurnal Tarbiyah Jamiat Kheir, 2025)
Abstract Background: The formation of leadership character from an early age has become an urgent need in facing global challenges in the current era. Student organizations at the elementary school level have the potential to become strategic platforms for developing leadership character by integrating Muhammadiyah values. Objective: This research aims to analyze the role of student organizations in developing leadership character in elementary education through the implementation of Muhammadiyah values. Method: Descriptive qualitative research was conducted at MI Nurul Islam in South Tangerang City involving 80 students, 9 supervising teachers, and 1 principal. Data were collected through participatory observation, in-depth interviews, documentation, and focus group discussions. Results: Student organizations proved effective in developing six dimensions of leadership character: integrity, responsibility, effective communication, empathy, creativity, and cooperation. The integration of Muhammadiyah values through noble character programs, social care, and the spirit of tajdid strengthened the formation of leadership character. Conclusion: The leadership character development model through student organizations with a Muhammadiyah values approach proved capable of forming prospective leaders with integrity and noble character from an early age. Keywords: leadership character, student organizations, elementary education, Muhammadiyah values, character development